2012
DOI: 10.1142/s0219843612500132
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Mechanical Designed Prosthetic Hand With Multi-Control Strategies

Abstract: In order to mimic the natural appearance, motion, and perception of the human hand, a biomechatronic approach to design an anthropomorphic prosthetic hand À À À HIT/DLR Prosthetic Hand has been presented. It reproduces human hand in its fundamental structure such as appearance, weight, and dimensions. Its thumb can move along a cone surface in 3D space. Similar with that of human's, it combines with abduction and adduction from palmar position to lateral position. Actuated by only one motor, the middle¯nger, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Also, the participants in Choi et al, (2017) study received a stimulation on the upper arm, which enabled them to perceive the pressure that the prosthesis applied on the surface [75]. Equally, the participants of Huang et al, (2012) by receiving a stimulaton on forearm, were able to perceive the applied force [44]. Finally, Chai et al, (2019) showed that the electrotactile feedback on the forearm facilitates a discrimination of the size and texture (i.e., hardness and softness) of the target object, and it also assists with differentiation of the applied grasping force [73].…”
Section: Biomedical Applications: Prosthesesmentioning
confidence: 99%
“…Also, the participants in Choi et al, (2017) study received a stimulation on the upper arm, which enabled them to perceive the pressure that the prosthesis applied on the surface [75]. Equally, the participants of Huang et al, (2012) by receiving a stimulaton on forearm, were able to perceive the applied force [44]. Finally, Chai et al, (2019) showed that the electrotactile feedback on the forearm facilitates a discrimination of the size and texture (i.e., hardness and softness) of the target object, and it also assists with differentiation of the applied grasping force [73].…”
Section: Biomedical Applications: Prosthesesmentioning
confidence: 99%
“…Most haptic interfaces are therefore designed and developed for the fingers and the hands [6], [8]. In this respect, Kaczmarek et al, (2017) found that users Acceptability/Suitability [17], [24], [25], [26], [27], [28] [22], [29], [30], [31], [32], [33], [34] 1 -21 Tactile Sensation [35], [36], [37], [38], [39] [22], [33], [34], [40] 1 -21 Free Electrodes; Touchpad; Armband None; Prosthetic hand Index & Middle Fingertip; Forearm; Palm Touch Rendering [20], [24], [41], [42], [43], [44] [45], [46], [47], [48], [49], [50] [19], [51], [52], [53], [54], [55] were able to accurately differentiate the frequency and intensity of electrotactile feedback on middle fingertip [27]. Notably, the acceptability of receiving electrotactile feedback on the index fingertip has been examined and confirmed by two user studies with an adequate sample size (e.g., N = 15 or 21) [24], [25].…”
Section: Epidermal Stimulationmentioning
confidence: 99%
“…14 A¯ve-¯ngered underactuated prosthetic hand controlled by surface electromyographic signals is presented and it has the same function to the Laval hand. 15,16 These two hands can adapt di®erent objects passively, but they cannot actuate distal joints in free environment and thus they cannot be well tō nish precision tasks.…”
Section: Introductionmentioning
confidence: 99%